An Educational Outreach on The Health Benefits of Vitamin C and A Demonstration of Its Testing Methods at MAN 3 Pontianak - Dwisari, Fath; Dermawan, Abdurraafi' Maududi; Tjoadri, Tessa Nathalia; Jumadilah, Rahmi; Afriani, Natia (BADAN PENERBIT STIEPARI PRESS, 2025)
The impact of neglecting vitamin intake, particularly vitamin C, extends beyond diminished immune function to include a reduction in metabolic processes, which can subsequently impair learning concentration and lead to declines in academic performance and nutritional status among students. Vitamin C is an essential micronutrient crucial for human health, serving as a potent antioxidant and bolstering the immune system. This study aims to provide education on various sources of vitamin C and its health benefits, as well as demonstrate vitamin C identification among students at MAN 3 Pontianak. This research is a descriptive design with a one-group pretest-posttest framework, involving 30 respondents. The findings reveal that out of 30 students (100%), the majority were aged 16 years, comprising 22 individuals (73.3%). The predominant gender among respondents was female, with 20 individuals (66.7%), while male respondents numbered 10 (33.3%). Prior to the educational intervention, student knowledge was categorized as good for 17 individuals (56.7%), adequate for 12 individuals (40%), and poor for 1 individual (3.3%). Following the educational intervention, all 30 students (100%) were classified as having good knowledge. This indicates a significant enhancement in the overall knowledge of vitamin C sources and their health benefits among students at MAN 3 Pontianak after the educational program.